2020
DOI: 10.1093/advances/nmaa010
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Relation between Tea Consumption and Risk of Cardiovascular Disease and All-Cause Mortality: A Systematic Review and Meta-Analysis of Population-Based Studies

Abstract: Tea flavonoids have been suggested to offer potential benefits to cardiovascular health. This review synthesized the evidence on the relation between tea consumption and risks of cardiovascular disease (CVD) and all-cause mortality among generally healthy adults. PubMed, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, Food Science and Technology Abstracts, and Ovid CAB Abstract databases were searched to identify English-language publications through 1 November 2019, including randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 77 publications
1
73
0
Order By: Relevance
“…Cardiovascular disease (CVD) is the leading cause of deaths worldwide. A number of recent meta-analyses of prospective cohort studies have indicated that individuals with the highest flavonoid intakes have lower relative risk of mortality from CVD and all-causes compared with that of individuals with the lowest intakes [111][112][113]. Several studies evidenced the beneficial effects of Allium flavonols on the cardiovascular system via their regulatory effects on platelet aggregation [83,84,96], atherogenesis [78], thrombotic activities [79], endothelial function [81], hypertension [77,82], lipid metabolism [77], and oxidative stress [42] (Table 3).…”
Section: Cardio-protective Effectsmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of deaths worldwide. A number of recent meta-analyses of prospective cohort studies have indicated that individuals with the highest flavonoid intakes have lower relative risk of mortality from CVD and all-causes compared with that of individuals with the lowest intakes [111][112][113]. Several studies evidenced the beneficial effects of Allium flavonols on the cardiovascular system via their regulatory effects on platelet aggregation [83,84,96], atherogenesis [78], thrombotic activities [79], endothelial function [81], hypertension [77,82], lipid metabolism [77], and oxidative stress [42] (Table 3).…”
Section: Cardio-protective Effectsmentioning
confidence: 99%
“…Brewed tea ( Camellia sinensis ) is a major dietary source of flavonoids, in particular flavan-3-ols [ 1 ]. Results of population studies commonly suggest that tea consumption is inversely associated with several health outcomes [ 2 ]. Shorter-term clinical intervention studies provide additional evidence that tea consumption has the potential to affect intermediate outcomes and biomarkers of disease in healthy, at-risk, and diseased populations [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shorter-term clinical intervention studies provide additional evidence that tea consumption has the potential to affect intermediate outcomes and biomarkers of disease in healthy, at-risk, and diseased populations [ 3 , 4 ]. Several recent systematic reviews have demonstrated these distinct effects, particularly in regard to cardiovascular disease (CVD) [ 2–4 ], the leading cause of death worldwide [ 5 , 6 ]. In the presence of suboptimal fruit, vegetable, and whole grain intake [ 7 ], unsweet tea may have increased potential to improve human health by providing consumers plant-derived dietary bioactive compounds such as flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Camellia sinensis use is also associated with a more favorable cardiovascular disease risk profile [ 28 ]. The positive impact of green tea on cardio-metabolic health is related to its high content of polyphenols, in particular catechins, such as epicatechin (EC), epigallocatechin (EGC), epicatechin-3-gallate (ECG), and epigallocatechin-3-gallate (EGCG) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%